METHOD OF CALCULATION OF HASSE-WITT MATRIX WITH HYPERELLIPTIC CURVES OF SPECIAL KIND - Dolgov, V. I.; Nelasaya, A. V. (Radio Electronics, Computer Science, Control, 2008)
The method for calculating Hasse-Witt matrix for special hyperelliptic curves are proposed. This method is based on using binomial theorem.